Dopant-induced shape evolution of polyhedral magnetite nanocrystals and their morphology/component-dependent high-rate electrochemical performance for lithium-ion batteries. Issue 58 (1st June 2016) - Ding, Chuan; Zeng, Yanwei; Cao, Liangliang; Li, Rongjie; Zhang, Yuan; Zhao, Longfei
Abstract : Mn doped Fe3 O4 polyhedrons are shown to have component-related morphology evolution and crystal plane-dependent electrochemical performance when used as high-rate anode materials for LIBs. Abstract : Monodisperse Mn x Fe3− x O4 ( x = 0, 0.3, 0.6) polyhedrons enclosed by {100}/{111} facets with different area ratios were synthesized through the thermolysis of Fe(acac)3 and Mn(acac)2 by effectively tuning the Mn/Fe ratio to mediate the adsorption properties of oleic acid (OA) on crystal surfaces after annealing treatment in N2, and studied as high rate (≥1 A g −1 ) anode materials for lithium ion batteries (LIBs). The electrochemical results show that Mn0.6 Fe2.4 O4 octahedra possess the best rate cycling performance compared to that of Mn0.3 Fe2.7 O4 cuboctahedra and Fe3 O4 cubes, characterised by a 500th discharge capacity of 803.5 mA h g −1 at 1 A g −1 and a rate capability of 661.5 mA h g −1 when cycled at 4 A g −1, as a result of high electrochemical activity of {111} facets with the highest Fe atom surface density. The present results prove that the substitution of Fe by Mn in the spinel-type anode materials can result in better cycle stability and it would be helpful for the further understanding of Fe3 O4 based anode materials and provide a simple and practical route to design high rate anode materials for lithium-ion batteries.